Ejection of Quasi-Free-Electron Pairs from the Helium-Atom Ground State by Single-Photon Absorption - Schöffler, M. S.; Stuck, C.; Waitz, M.; Trinter, F.; Jahnke, T.; Lenz, U.; Jones, M.; Belkacem, A.; Landers, A. L.; Pindzola, M. S.; Cocke, C. L.; Colgan, J.; et al. (My University, 2013)
We investigate the single-photon double ionization of helium at photon energies of 440 and 800 eV. We observe doubly charged ions with close to zero momentum corresponding to electrons emitted back to back with equal energy. These slow ions are the unique fingerprint of an elusive quasifree photon double ionization mechanism predicted by Amusia et al. nearly four decades ago [J. Phys. B 8, 1248 (1975)]. It results from the nondipole part of the electromagnetic interaction. Our experimental data are supported by calculations performed using the convergent close-coupling and time-dependent close-coupling methods.